Environmental Influence on the Use of Abusive Language and Solutions through the NABA Program at SDN-SN Kuripan 2 - Fatihah, Dea Amani; Kuramah, Najwa; Faulina Barus, Cesillia; Wulandari, Chairunnisa; Rizqy Ramadhani, Muhammad; Laily Anggraini, Noor; Ilma, Rosiha; Hidayat, Ari (TROPICAL WETLAND JOURNAL, 2025)
The surrounding environment is one of the primary factors influencing children's behavior. The environment has the potential to exert both positive and negative influences. This study aims to explore the impact of the surrounding environment on the behavior of elementary school students. The research employs a qualitative descriptive approach, with data collected through observation and interviews. Field findings indicate that negative environmental influences can lead to undesirable behaviors among students, such as the tendency to use inappropriate language in communication. This study is expected to be followed up with the implementation of the "Goodness Advice Program" (NABA), which focuses on habituating students to consistently exhibit positive behavior. For more severe issues, schools are encouraged to collaborate with parents and the community to provide appropriate parenting support.